Reasons for relating representations when reading digital multimodal science information. (August 2018) - Sivle, Anders D; Uppstad, Per H
This exploratory study examined 16 participants' reasons for relating representations when reading online information that presented weather forecasts comprising a variety of representations. They were told to advise a friend, who was planning to paint the exterior of his house, based on the online information. The participants' multimodal reading was tracked with a SMI RED (50 Hz) eye-tracker, and their reasons for relating representations were investigated through a retrospective think-aloud protocol cued by the recording of the individual's reading behaviour and a stand-alone interview. In line with expected behaviour, results suggest that decision-making processes influenced the construction of reading paths. More interestingly, results showed that the participants' reasons for making transitions between representations were to control and compare information. The discussion focuses on this study's unique contribution in terms of new conjectures for future research.